Role of Tarentula in Autism Spectrum Disorder- A Case Report (Advancements in Homeopathic Research, 2024)
Background: Autism Spectrum Disorder (ASD)  is a complex neurodevelopmental condition with  limited treatment options. This case series explores  the potential of homeopathic Tarentula in managing  ASD symptoms.  Method: Two cases of moderate ASD (ISAA scores  132 and 151) were treated with Tarentula 200C  for 1 year. Monthly follow-ups assessed progress  using ISAA scores, caregiver reports, and clinical  observations.  Result: Both cases showed significant improvement.  Case 1 (ISAA 132) achieved non-autistic status  (ISAA 44) after 12 months. Case 2 (ISAA 151)  achieved non-autistic status (ISAA 65) after 12  months. Caregivers reported satisfaction with the  treatment.  Conclusion: This case series suggests a potential  role for Tarentula in improving ASD symptoms,  particularly in moderate cases. However, further  well-designed research is needed for stronger  evidence. Key Words: Autism Spectrum Disorder,  Homoeopathy, Tarentula,Indian Scale for Assessment  of Autism
Keywords: autism aetiology; symptom